2021
DOI: 10.1093/genetics/iyab084
|View full text |Cite
|
Sign up to set email alerts
|

Smoothened and ARL13B are critical in mouse for superior cerebellar peduncle targeting

Abstract: Patients with the ciliopathy Joubert syndrome present with physical anomalies, intellectual disability, and a hindbrain malformation described as the “molar tooth sign” due to its appearance on an MRI. This radiological abnormality results from a combination of hypoplasia of the cerebellar vermis and inappropriate targeting of the white matter tracts of the superior cerebellar peduncles. ARL13B is a cilia-enriched regulatory GTPase established to regulate cell fate, cell proliferation and axon guidance through… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 99 publications
0
17
0
Order By: Relevance
“…The most parsimonious interpretation is that Chlamydomonas ARL13 is not acting via its GEF activity through ARL3 to prevent PLD accumulation in cilia. In related observations, mice expressing Arl13b R79Q/R79Q , a derivative with impaired GEF-activity for Arl3, were shown to develop normally ( Suciu et al, 2021 ). Thus, two widely used models for ciliopathies do not recapitulate the grave effects of ARL13b mutations with diminished GEF activity on humans.…”
Section: Resultsmentioning
confidence: 92%
“…The most parsimonious interpretation is that Chlamydomonas ARL13 is not acting via its GEF activity through ARL3 to prevent PLD accumulation in cilia. In related observations, mice expressing Arl13b R79Q/R79Q , a derivative with impaired GEF-activity for Arl3, were shown to develop normally ( Suciu et al, 2021 ). Thus, two widely used models for ciliopathies do not recapitulate the grave effects of ARL13b mutations with diminished GEF activity on humans.…”
Section: Resultsmentioning
confidence: 92%
“…This work found that in arl13b morphant (and mutant) larvae, the number of cerebellar granule cells was reduced and the development of Purkinje cells was also affected, anomalies that were linked to defective WNT signaling. Of note, the described central nervous system phenotypes were relatively mild compared to the anomalies found in mouse models for Arl13b (Higginbotham et al, 2012;Suciu et al, 2021) or in human patients harboring ARL13B mutations (Cantagrel et al, 2008;Thomas et al, 2015). No other studies have described cerebellar anomalies in zebrafish JBTS models yet, whereby it remains unclear how thoroughly the central nervous system has been analyzed in the published zebrafish JBTS models to date.…”
Section: Comparison Between Zebrafish Mutants In Joubert Syndrome Genesmentioning
confidence: 94%
“…Dendrogram based on [130] and [422] 458]. While the molecular mechanisms causing scp misrouting are incompletely characterized, the ciliary axoneme protein Arl13b regulates scp guidance, which relies on non-cell autonomous Hedgehog signaling [459]. Changes in ARL13B expression cause abnormalities in growth cone dynamics and axonal tract development [458,460].…”
Section: The Cerebellar Nuclei and Joubert Syndromementioning
confidence: 99%